Nonrandom Distribution of Antlers Cast by Peary Caribou Bulls, Melville Island, Northwest Territories - Miller, Frank L.; Barry, Samuel J. (ARCTIC, 1992)
An aerial survey was carried out in July 1987 to determine the pattern of distribution of antlers cast by Peary caribou (Rangifer tarandus pearyi) bulls on north-central and northeastern Melville Island, Northwest Territories, Canada. Four transect lines were flown parallel to the coastal shorelines of Hecla and Griper Bay and adjacent Sabine Bay at distances of about 0.8, 2.4, 5.0, and 10.0 km inland. A four-person survey crew was used in a Bell-206B turbo-helicopter flown at about 90 m above ground level and at an air speed of about 160 km/h. We recorded 531 antlers cast by bulls along ca. 1110 km of transects: 55% within 1.6 km of the seacoast and 89% within 3.2 km. Antlers were not randomly distributed along or among transects (p<0.05). The antlers were clumped in distribution and their numbers declined significantly with distance from the seacoast (p<0.05). We suggest that use of such coastal rutting areas by low-density populations of Peary caribou would confer, without any precognition or anticipation on the part of the animals, maximal timely contact between rutting bulls and cows in heat during the short temporal peak of the autumn rut by reducing a two-dimensional search problem to an essentially linear one.Key words: Peary caribou, Rangifer tarandus pearyi, bulls, cast antlers, Melville Island, Northwest Territories RÉSUMÉ. Un relevé aérien a été effectué en juillet 1987 pour déterminer le schéma de distribution des bois perdus par les caribous de Peary (Rangifer tarandus pearyi) mâles dans le centre-nord et le nord-est de l’île Melville, dans les Territoires du Nord-Ouest au Canada. Quatre transectsont été survolés, parallèlement au rivage le long de Hecla et de Griper Bay et de la baie adjacente, Sabine Bay, à des distances d’environ 0,8, 2,4,5,0 et 10,0 km à l’intérieur des terres. Une équipe composée de quatre individus a effectulee relevé partir d’un hélicoptere à turboréacteur Bell-206B,volant à environ 90 m du sol et à une vitesse aérodynamique de 160 km.h . On a relevé 531 bois perdus ...